Preliminary study of the mechanism of isolinderalactone inhibiting the malignant behavior of bladder cancer - Qun Wang; Wenkai Xu; Lu Ying; Hongjin Shi; Yuxin Sun; Wei Feng; Haole Xu; Jun Xie; Hairong Wei; Zhao Yang; Haifeng Wang (Current Urology)
Abstract. Background. Isolinderalactone (ILL), extracted from the dried tubers of Linderae aggregate, has multiple functions, such as antioxidation, antitumor, and anti-infection effects. However, there have been few studies on ILL's antitumor role and no reports on its role in bladder cancer (BC). Materials and methods. Human BC cell lines T24 and EJ-1 were treated with different concentrations of ILL (0, 10, 20, 50, 100, 200, 400, 600, 800, and 1000 μmol/L), and the cell proliferation inhibition rate was analyzed using the CCK-8 assay. The effect of ILL on T24 and EJ-1 cell cycle inhibition and apoptosis was examined using flow cytometry. Immunoblotting was used to detect the levels of apoptosis-related proteins, BAX, BAK1, and CYCS, in BC cells of the control and ILL-treated groups, and quantitative PCR experiments were performed to detect the apoptosis-related gene expression of CASP10, CYCS, BAX, BCL-2, CASP8, and BAK1. T24 and EJ-1 tumor-bearing mouse models were established and divided into vehicle control, low-dose (10 mg/kg) and high-dose (20 mg/kg) groups, with 5 mice in each group. Hematoxylin and eosin staining and immunohistochemistry were used to detect changes in apoptosis-related proteins in vivo. Results. The CCK-8 assay showed that in vitro, ILL significantly inhibited the proliferation of the T24 and EJ-1 BC cell lines. Flow cytometry and immunoblotting results showed that ILL increased mitochondrial permeability by upregulating proapoptotic proteins BAK1 and BAX, promoting CYCS release and significantly inducing cell cycle arrest at G0/G1 phase. In vivo, on day 25 of administration, tumor inhibition rates in T24 and EJ-1 tumor-bearing mice were up to 75.24% and 47.43%, respectively, in the ILL high-dose–treated and 71.58% and 43.89%, respectively, in the ILL low-dose–treated groups. Conclusions. Isolinderalactone controls BC progression by inducing apoptosis, suggesting that ILL may be an effective drug for the treatment of BC.